Hybridization-facilitated genome merger and repeated chromosome fusion after 8 million years - Mandáková, Terezie; Guo, Xinyi; Özüdoğru, Barış; Mummenhoff, Klaus; Lysak, Martin A (The Plant journal, 2018)
The small genus Ricotia (nine species, Brassicaceae) is confined to the eastern Mediterranean. By comparative chromosome painting and a dated multi-gene chloroplast phylogeny, we reconstructed the origin and subsequent evolution of Ricotia. The ancestral Ricotia genome originated through hybridization between two older genomes with n = 7 and n = 8 chromosomes, respectively, on the Turkish mainland during the Early Miocene (c. 17.8 million years ago, Ma). Since then, the allotetraploid (n = 15) genome has been altered by two independent descending dysploidies (DD) to n = 14 in Ricotia aucheri and the Tenuifolia clade (2 spp.). By the Late Miocene (c. 10 Ma), the latter clade started to evolve in the most diverse Ricotia core clade (6 spp.), the process preceded by a DD event to n = 13. It is noteworthy that this dysploidy was mediated by a unique chromosomal rearrangement, merging together the same two chromosomes as were merged during the origin of a fusion chromosome within the paternal n = 7 genome c. 20 Ma. This shows that within a time period of c. 8 Myr genome evolution can repeat itself and that structurally very similar chromosomes may originate repeatedly from the same ancestral chromosomes by different pathways (end-to-end translocation versus nested chromosome insertion).
Keywords: molekulární evoluce; Turecko; Chromosome Painting; ancient polyploidy; Genome, Plant; chromosomal rearrangements; Brassicaceae; genom rostlinný; karyotypizace; Turkey; Chromosomes, Plant; Karyotyping; karyotype evolution; hybridization; ploidie; diploidization; Ricotia; malování chromozomů; Ploidies; fylogeneze; Chromosome Aberrations; Hybridization, Genetic; chromozomální aberace; chromozomy rostlin; hybridizace genetická; dysploidy; Phylogeny; Evolution, Molecular